Teacher Preparation, Motivation, and Self-Efficacy: A Comparative Study of New Teachers in Japan and the United States - Shaoan Zhang; Andromeda Hightower; Qingmin Shi (Indonesian Journal Of Educational Research and Review, 2021)
Using the Teaching and Learning International Survey (TALIS) 2018, this study examines U.S. and Japanese new teachers’ initial teacher preparation (ITP), feelings of preparedness, motivations, and self-efficacy. The analysis of 355 U.S. and 433 Japanese new secondary teachers provided several findings. First, ITP in the U.S. more often included teaching in mixed-ability and multicultural settings, cross-curricular skills, and technology than Japan, and U.S. teachers felt more prepared than Japanese teachers in every category of preparation. Second, Japanese teachers were more likely to declare teaching as their first career choice and reportedly scored significantly higher on motivations to become a teacher of personal utility value, while U.S. new teachers scored higher on social utility value. Third, there were no significant differences in self-efficacy between U.S. and Japanese new teachers. This study contributes to the gap of large-scale, comparative literature between the U.S. and Japanese initial teacher preparation. Implications for practice and directions for future research are discussed.